Pigment profile in the photosynthetic sea slug Elysia viridis (Montagu, 1804) - Cruz, Sónia
Some sacoglossan sea slugs are capable of retaining functional chloroplasts stolen' from macroalgae (kleptoplasts). The present study surveyed the pigment composition of the sea slug Elysia viridis (Montagu, 1804) and its food source Codium tomentosum from three different locations along the Portuguese coast. The pigments siphonaxanthin, trans and cis-neoxanthin, violaxanthin, siphonaxanthin dodecenoate, chlorophyll (Chl) a and Chl b, {varepsilon},{varepsilon}- and {beta},{varepsilon}-carotenes and an unidentified carotenoid were observed in all E. viridis analysed. With the exception of the unidentified carotenoid, the same pigment profile was recorded for the macroalga C. tomentosum. Pigments characteristic of other macroalgae present in the sampling locations (Ulva sp. or the epiphyte Ceramium sp. present on C. tomentosum) were not detected in the slugs (Chl c, fucoxanthin, lutein, {beta},{beta}-carotene). These results suggest that E. viridis retained chloroplasts exclusively from C. tomentosum. The differentiation between sea slugs and respective food source from different locations indicated that the site of collection was less relevant to the separation of groups than differences between the macroalgae and the sea slugs. In general, the carotenoids to Chl a ratios were significantly higher in E. viridis than in C. tomentosum. Further analysis using starved individuals suggests carotenoid retention over Chls during the digestion of kleptoplasts. Finally, despite a loss of 80% of Chl a in E. viridis starved for 2 weeks, measurements of maximum quantum yield of photosystem II (Fv/Fm) using variable Chl a fluorescence indicated a decrease of only 5% of the photosynthetic capacity of kleptoplasts.